Educational Reception in Rotterdam and Barcelona : Policies, Practices and Gaps - Bruquetas-Callejo, Maria (Book collections on Project MUSE., 2014)
This book takes a close look at how schools and educators in Rotterdam and Barcelona handle the reception of new immigrant students, focusing on the dilemmas educators face in attempting to integrate the new students into the school and classroom and the strategies they design as a response. In addition to comparing the two cities' approaches, María Bruquetas-Callejo pays particular attention to how closely actual practices hew to policies.